Advances in Soil Ecosystem Services: Concepts, Models, and Applications for Earth System Life Support. Issue 4 (19th July 2013) - Robinson, D.A.; Jackson, B.M.; Clothier, B.E.; Dominati, E.J.; Marchant, S.C.; Cooper, D.M.; Bristow, K.L.
Abstract : The ecosystem services approach is gaining wide acceptance at the policy‐making level as a framework for integrating science and policy regarding the natural environment. It is important that soil science clearly articulates how knowledge and understanding of the vadose zone soils can be transmitted through this framework into the decision‐making process. Competition between food production, living space, and maintaining habitat for all of earth's life‐forms has never been so intense, so the need for soil security and vadose zone protection is paramount. Soil management can no longer be thought of in terms of single function management but instead needs to be considered and managed in the context of the multiple functions it offers. In this 10th anniversary issue of the journal, we assess progress in the development of a coherent soil ecosystem services framework using the natural resource management stock‐flow and fund‐service resource approach. We go on to examine some of the areas where the application of an ecosystems approach is gaining traction, which include national and local decision making as well as support for legal arguments in court.